REKSA DANA SEBAGAI SALAH SATU ALTERNATIF INVESTASI - Meilinda . (Center for Economic Studies Universitas Katolik Parahyangan, 2010)
An investor always search for the best investment to protect and grow his/her wealth. There are many investment instruments that provide high-return with high-risk and vice versa. Choosing the right instrument for an investor may depend on the risk profiles, amount of fund, time horizon, knowledge and the goal to achieve. Despite of the risks, mutual/investment fund is one of the profitable investment instruments.Keywords : investment, return, risk profiles, mutual investment fund